2016
DOI: 10.21649/akemu.v22i4.1458
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Type 1 Diabetes Mellitus in Saudi Children: a Hospital Based Study

Abstract: Objective: To determine the clinical characteristics of newly diagnosed type 1 diabetes mellitus (T1DM) in children under15 years of age. Cross sectional study conducted at Aseer Central Hospital Abha, Southwestern Saudi Arabia from June 2011 -May 2015. Patients and Methods: Study included 141 Saudi children, < 15 years old with newly diagnosed T1DM. The demographic and laboratory data were collected from file records. The patients were divided into younger (< 5 yr), middle (5 -10 yr) and older (>10 -15 yr)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The commonest symptom being polyuria 33 (78.6%) followed by polydipsia 27 (64.3%), weight loss 23 (54.8%) and polyphagia 13 (30.9%) which is comparable to other studies. 11,20 In present study, family history of diabetes in first degree relative was 9 (21.4%) which is similar to the studies from India (26.4%) and Bangladesh (22.2%). 12,21 In contrast, studies from Saudi Arab (34%) and Libya (48%) revealed high prevalence of family history of diabetes.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The commonest symptom being polyuria 33 (78.6%) followed by polydipsia 27 (64.3%), weight loss 23 (54.8%) and polyphagia 13 (30.9%) which is comparable to other studies. 11,20 In present study, family history of diabetes in first degree relative was 9 (21.4%) which is similar to the studies from India (26.4%) and Bangladesh (22.2%). 12,21 In contrast, studies from Saudi Arab (34%) and Libya (48%) revealed high prevalence of family history of diabetes.…”
Section: Discussionsupporting
confidence: 88%
“…10 In contrast, studies from Saudi Arabia (6.8±3.2 years) and Bangladesh (9±3.9 years) reported younger age of onset. 11,12 Minimum age at the time of diagnosis in present study was 17 months. Mean duration of symptoms before diagnosis was more than two weeks which is comparable to a study from Europe.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Classic symptoms like polyuria, polydipsia, weight loss were the main presenting symptoms in our study population, similar observation was reported in other studies also. 12,13,14 In this study Diabetic ketoacidosis at initial presentation was noticed in more than half of the subjects. The reported frequency of DKA as the primary presentation varies from 15 -67% in type I diabetes in children.…”
Section: Discussionmentioning
confidence: 60%